Cost‐effectiveness of transoral robotic surgery versus (chemo)radiotherapy for early T classification oropharyngeal carcinoma: A cost‐utility analysis. Issue 4 (30th June 2015) - de Almeida, John R.; Moskowitz, Alan J.; Miles, Brett A.; Goldstein, David P.; Teng, Marita S.; Sikora, Andrew G.; Gupta, Vishal; Posner, Marshall; Genden, Eric M.
Abstract: Background: The present study is an economic evaluation comparing transoral robotic surgery (TORS) to (chemo)radiotherapy for the management of early T‐classification oropharyngeal cancer. Methods: A societal perspective was adopted. Treatment for TORS and (chemo)radiotherapy were modeled using decision analysis and recurrences were modeled over a 10 year horizon with a Markov model. Model parameters were derived from systematic review. Deterministic and probabilistic sensitivity analyses were used to test model robustness. Results: TORS demonstrated a cost savings of 1366 and an increase of 0.25 quality‐adjusted life years (QALYs) per case in comparison to (chemo)radiotherapy. TORS was sensitive to variations in adjuvant therapy, costs, utilities, complications, and recurrence rates in deterministic and probabilistic sensitivity analysis. In two‐way sensitivity analysis, with increasing adjuvant therapy for TORS and decreasing concurrent chemotherapy for radiotherapy, TORS is decreasingly cost‐effective. Conclusion: TORS is cost‐effective for treatment of early oropharyngeal cancer. Case selection to minimize adjuvant therapy ensures cost‐effective treatment. © 2015 Wiley Periodicals, Inc. Head Neck 38: 589–600, 2016